2014
DOI: 10.1016/j.ecoenv.2014.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in major marketed marine bivalves from six northern coastal cities of China: Concentrations and risk assessment for human health

Abstract: a b s t r a c tOne hundred and fifty nine samples of nine edible bivalve species (Argopecten irradians, Chlamys farreri, Crassostrea virginica, Lasaea nipponica, Meretrix meretrix, Mytilus edulis, Ruditapes philippinarum, Scapharca subcrenata and Sinonovacula constricta) were randomly collected from eight local seafood markets in six big cities (Dalian, Qingdao, Rizhao, Weifang, Weihai and Yantai) in the northern coastal areas of China for the investigation of trace element contamination. As, Cd, Cr, Cu, Hg, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…During the last decade, several studies have investigated metal contaminants in surface water, sediment, as well as aquatic organisms along the north coast of the Shandong Peninsula (Liang et al, 2004;Wang et al, 2005;Xu et al, 2013;Gao et al, 2014;Li and Gao, 2014). In the present study, chemical analysis of oyster tissues was performed to identify contaminant conditions, and several physiological parameters and biomarkers indicative of oxidative stress, neurotoxicity and genotoxicity were also investigated to assess the health status of selected organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, several studies have investigated metal contaminants in surface water, sediment, as well as aquatic organisms along the north coast of the Shandong Peninsula (Liang et al, 2004;Wang et al, 2005;Xu et al, 2013;Gao et al, 2014;Li and Gao, 2014). In the present study, chemical analysis of oyster tissues was performed to identify contaminant conditions, and several physiological parameters and biomarkers indicative of oxidative stress, neurotoxicity and genotoxicity were also investigated to assess the health status of selected organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The north coast of the Shandong Peninsula, located along the southern Bohai Sea, is one of the most important economic zones and industrial clusters in Northeast China. Heavy metals distribution and contamination in the surface seawater and sediment (Xu et al, 2013;Gao et al, 2014) as well as bivalve species (Liang et al, 2004;Wang et al, 2005;Li and Gao, 2014) have been documented in this region. However, there is little information about biological effects-based monitoring of such metal contamination in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Mora et al (2004) found low concentrations of As in sediments from Gulf and Gulf of Oman and high concentration in bivalves (Pinctada radiata, Crassostrea virginica, Saccostrea cucullata, Mytilus edulis). According to Li and Gao (2014), R. philippinarum from northern coastal of China was one of the bivalve species that accumulated higher concentrations of As when compared with C. gigas and M. edulis.…”
Section: Concentration Of Elementsmentioning
confidence: 98%
“…The north coast of the Shandong Peninsula, located along the southern Bohai Sea, is one of the most important economic zones and industrial clusters in Northeast China. Heavy metals distribution and contamination in the surface seawater and sediment (Xu et al, 2013;Gao et al, 2014) as well as bivalve species (Liang et al, 2004;Wang et al, 2005;Li and Gao, 2014) have been documented in this region. However, there is little information about biological effects-based monitoring of such metal contamination in this region.…”
Section: Introductionmentioning
confidence: 96%